Pengaruh Citra, Reputasi dan Kualitas Pelayanan terhadap Kepuasan dan Loyalitas Mahasiswa PTS di Jawa Timur (Studi pada STIE dengan Program Studi Terakreditasi) - Wantara, Pribanus (Jurnal Aplikasi Manajemen, 2009)
The objectives of this research are to examine and analyze: (1) whether the image of STIE influences students' satisfaction; (2) whether the image of STIE influences students' loyalty; (3) whether the reputation of STIE influences students' satisfaction; (4) whether the reputation of STIE influences students' loyalty; (5) whether the service quality of STIE influences students' satisfaction; (6) whether the service quality of STIE influences students' loyalty; (7) whether the students' satisfaction influences students' loyalty. Theoretically, the results of this research are to enrich and strengthen the science of marketing especially customer's behavior theory. The research object was a number of accredited study programs of 12 STIE in Kopertis Wilayah VII - East Java. The number of respondents was 200 students. This is a causality research. The variables were measured using Likert Scale with 1 - 5 ladders. Structural Equation Modeling (SEM) with software AMOS 5 was used to test hypothesis. The finding of the research can be described into two categories: 1. Supporting the previous research i.e.: a). Iof significantly influenced (directly and positively) students' satisfaction and loyalty; b). Reputation of significantly influenced (directly and positively) students' satisfaction and loyalty; c). Service quality of significantly influenced (directly and positively) students' satisfaction; and d). Students' satisfaction significantly influenced (directly and positively) students' loyalty; and 2. Not supporting the previous research i.e.: Service quality of did not significantly influenced students' loyalty.